2010
DOI: 10.1111/j.1600-0560.2010.01556.x
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphatic histiocytosis following placement of a metal implant

Abstract: Intralymphatic histiocytosis (IH) is a rare condition first reported in 1994 by O'Grady et al. Less than 40 cases have been reported, with the majority occurring in patients with rheumatoid arthritis. We present a case of a 72-year-old man who developed an asymptomatic rash on his left upper arm 3 years after placement of a metal implant to stabilize a fractured humerus. Examinations revealed a poorly demarcated erythematous to brown indurated plaque with a pebbly surface overlying the inferior portion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 10 publications
1
33
0
2
Order By: Relevance
“…Thus, it should be noted that intralymphatic histiocytosis occurs not only by association with RA, but also with other lymphostatic conditions like breast cancer and joint replacement. Grekin et al [7] and Rossari et al [8] also reported cases with metal implantation. In 2011, Sakaguchi et al [9] reported a case of intralymphatic histiocytosis that was improved by the use of anti-TNFα treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it should be noted that intralymphatic histiocytosis occurs not only by association with RA, but also with other lymphostatic conditions like breast cancer and joint replacement. Grekin et al [7] and Rossari et al [8] also reported cases with metal implantation. In 2011, Sakaguchi et al [9] reported a case of intralymphatic histiocytosis that was improved by the use of anti-TNFα treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Das histologische Bild zeigt erweiterte, dünnwandige Gefäße in der retikulären Dermis, die mit ortsständi-gen Histiozyten mit hellem Zytoplasma, vesikulärem, nierenförmigem Zellkern sowie mit Neutrophilen und Lymphozyten ausgefüllt sind. Perivaskuläre Plasmazellen und Lymphozyten sind oft auffindbar [7].…”
Section: Intralymphatische Histiozytoseunclassified
“…Ebenfalls selten wurden Hauteinblutung im Sinne einer Vaskulitis oder Urtikaria durch Metallimplantate beschrieben [31]. Die histologische Untersuchung von implantatassoziierten lokalen Hauterscheinungen ist anzustreben, um seltenere Konstellationen wie retikuläre Erytheme [34] oder eine intralymphatische Histiozytose [35] [37]. Andererseits konnte bei Versagen nichtzementierter M-o-M-Hü endoprothetik die mögliche Relevanz einer Metallallergie in Zusammenschau mit periimplantärer Histologie erhärtet werden [33].…”
Section: Hautreaktionenunclassified